Effects of Lactoferrin on Sleep Conditions in Children Aged 12–32 Months: A Preliminary, Randomized, Double-Blind, Placebo-Controlled Trial - Miyakawa M; Kubo S; Oda H; Motoki N; Mizuki M; Tsukahara T; Tanaka M; Yamauchi K; Abe F; Nomiyama T (Nature and Science of Sleep, 2020)
Momoko Miyakawa,1 Shutaro Kubo,1 Hirotsugu Oda,1 Noriko Motoki,2 Masaru Mizuki,2 Teruomi Tsukahara,2 Miyuki Tanaka,1 Koji Yamauchi,1 Fumiaki Abe,1 Tetsuo Nomiyama2 1Food Ingredients and Technology Institute, R&D Division, Morinaga Milk Industry Co., Ltd, Zama, Kanagawa, Japan; 2Department of Preventive Medicine and Public Health, Shinshu University School of Medicine, Matsumoto, Nagano, JapanCorrespondence: Momoko MiyakawaFood Ingredients and Technology Institute, R&D Division, Morinaga Milk Industry Co., Ltd., 1-83, 5-Chome, Higashihara, Zama-City, Kanagawa-Pref. 252-8583, JapanTel +81 46252 3045Fax +81 46252 3017Email mo-miyakawa@morinagamilk.co.jpPurpose: To investigate preliminarily the effect of lactoferrin (LF)-fortified formula on sleep conditions in children.Study Design: A preliminary, randomized, double-blind, placebo-controlled trial.Methods: Healthy children between the ages of 12 and 32 months who attended nursery schools in Japan were divided into two groups and assigned a placebo or LF (48 mg/day)-fortified formula. Children’s sleep conditions were investigated before and after the 13-week intervention using the Japanese Sleep Questionnaire for Preschoolers (JSQ-P).Results: Altogether, 109 participants were randomized. Eight participants were eliminated due to lost to follow-up, withdrawal of consent, and ineligibility, with 101 participants (placebo, n = 48; LF, n = 53) included in the full analysis set (FAS) and used for analysis. Wake-up time, bedtime, and nighttime sleep were comparable between the two groups before and after intervention. The change in total JSQ-P T scores tended to improve in the LF group (placebo vs LF: 0.5 ± 6.5 vs − 1.9 ± 6.1, p = 0.074), in particular, morning symptoms significantly improved (grumpy in the morning, hard to wake-up, and hard to get out of bed) (placebo vs LF: 0.8 ± 6.2 vs − 1.9 ± 6.2, p = 0.028). A better trend was also observed in the LF group regarding restless legs syndrome (RLS)-motor (rubs feet at night and touches feet at night) (placebo vs LF: 2.3 ± 10.7 vs − 0.6 ± 13.5, p = 0.083) and insufficient sleep (stays up more than one hour later the day before a holiday and wakes up more than one hour later on a holiday) (placebo vs LF: 0.1 ± 9.8 vs − 1.7 ± 8.8, p = 0.095). No adverse drug reactions were found.Conclusion: LF intake may improve sleep condition, especially morning symptoms in children above one year of age.Keywords: lactoferrin, sleep, growing-up formula, children